Performance of Cellulose Oil Palm Fibre (COPF) in Stone Mastic Asphalt (SMA) Mix - Vasudevan, Jeyan (2001)
A large amount of money is allocated annually to reduce skid-related accidents due to pavement failures. It seems that the current Hot Mix Asphalt (HMA) could no longer cater for heavy loading vehicles. This indicates that an alternative asphalt technology has to be looked into seriously. As such, Stone Mastic Asphalt (SMA) technology with Cellulose Oil Palm Fibre (COPF) was developed. It is a gap-graded mix with high percentage of coarse aggregate. This mix was found to be performing very well for heavy loading traffic with the use of COPF. Fibre in SMA plays an important role to stabilise the mix and to minimise the draindown phenomena. This research aims to study the production and processing of the fibre and their performance in the SMA. The fibre production and processing was done using different types of pulping methods such as mechanical and chemical pulping. Each type of pulp products was analysed for its suitability as an anti-draindown agent by using the fibre-oil draindown test. In this study, the standard production and processing methods would be adjusted or modified if the pulp product failed the oil draindown test or otherwise. When the produced pulp is found to be suitahle as an anti-draindown agent, it was then added to the SMA mix to check its perfi)rmance. Complete mechanical and chemical analyses were also performed on the fibre to check its ability to form micromesh netting. Material selection of aggregate and asphalt was carried out in accordance with the specified standards. It was found that the selected material complied with SMA mix requirement. Besides that, determination of Optimum Asphalt Content (OAC) was carried out in accordance with the UPM in-house method. From the study OAC of 5.5% was obtained. In addition, a new method of determination of Optimum Fibre Content (OFC) was developed in the study. The OFC of Smartcel obtained through this method was 0.3%. A detailed comparative performance study of SMA mix was carried out with different types of fibres and without any fibres. The performance was determined by using Density and Void Analysis, Resilient Modulus Test, Marshall Stability Test, Indirect Tensile Test, Moisture Induced Damage Test, Fatigue Test, Static Creep Test, Cantabro and Draindown Test. Results from the analysis revealed that SMA with fibre was performing well. The entire analysis indicated that the performance of S MA with COPF fibre was far superior as compared to the other SMA with international fibres and SMA without any fibre. This shows that SMA with COPF fibre can used as a heavy duty, durable and high skid resistance road pavement in Malaysia.